2022
DOI: 10.33963/kp.a2021.0175
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of telemedicine devices in patients with severe heart failure with an implanted cardiac resynchronization therapy system during two years of observation

Abstract: Background: Heart failure (HF) remains a disease with a poor prognosis. Telemonitoring is a medical service aimed at remote monitoring of patients. Aim:The study aimed to identify the clinical relevance of non-invasive telemonitoring devices in HF patients.Methods: Sixty patients aged 66.1 (11) years, with left ventricular ejection fraction (LVEF) 26.3 (6.8)% underwent cardiac resynchronization therapy (CRT) implantation. They were randomly allocated to the control (standard medical care) or study (standard me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Wagenaar et al [ 57 ] I: UC + attention pathway adjusted to e- health (TM with e-Vita interactive platform) C1: UC + Website (Heartfailurematters.org) - Reminders to use it C2: UC (cardiologist + nurse) I: 150 C1: 150 C2: 150 I: 66.6 (11) C1: 66.7 (10.4) C2: 66.9 (11.6) I: 113 (75.3) C1: 112 (74.7) C2: 109 (72.7) I: I 69 (48.9) II 46 (32.6) III 17 (12.1) IV 9 (6.4) C1: I 57 (39.6) II 53 (36.8) III 17 (11.8) IV 17 (11.8) C2: I 57 (39.9) II 55 (38.5) III 24 (16.8) IV7 (4.9) I: 35.6 (11.2) C1: 35.2 (11.1) C2: 36.2 (10) NR 12 ESC 2016 guideline ≥ 3mo since Dx NR ≥ 18 years Able to fill out questionnaires and take BP and weight measurements Internet access All cause mort HF mort CV mort Hx HF # Days for HHF HR-QoL (MLHFQ) 19. Wita et al [ 58 ] I: TM with App in tab C: UC (Cardiology Clinic) I: 28 C: 32 I: 65.1 (11.7) C: 66.9 (9.3) I: 23 (82.1) C: 24 (75) NR I: 26.6 (7) C: 26.1 (6.7) I: Isq 13 (46.4) C: Isq 16 (50) 24 HF with reduced LVEF, candidates for CRT according to ESC 2013 guidelines NR NR All cause mort HHF SD standard deviation, IQR interquartile range, NYHA New York Heart Association, LVEF left ventricular ejection fraction, HF heart failure, Hx hospitalizations, C comparator, I intervention, Tx treatment, TM telemonitoring, MPh mobile phone, UC usual care, HT hypertensive, mo months, def definition, ESC European Society of Cardiology, OMT optimal medical therapy, ACEi angiotensin-converting enzyme inhibitor, ARB - II angiotensin II receptor antagonist, BB beta blocker, wk weeks, mort mortality, CV ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wagenaar et al [ 57 ] I: UC + attention pathway adjusted to e- health (TM with e-Vita interactive platform) C1: UC + Website (Heartfailurematters.org) - Reminders to use it C2: UC (cardiologist + nurse) I: 150 C1: 150 C2: 150 I: 66.6 (11) C1: 66.7 (10.4) C2: 66.9 (11.6) I: 113 (75.3) C1: 112 (74.7) C2: 109 (72.7) I: I 69 (48.9) II 46 (32.6) III 17 (12.1) IV 9 (6.4) C1: I 57 (39.6) II 53 (36.8) III 17 (11.8) IV 17 (11.8) C2: I 57 (39.9) II 55 (38.5) III 24 (16.8) IV7 (4.9) I: 35.6 (11.2) C1: 35.2 (11.1) C2: 36.2 (10) NR 12 ESC 2016 guideline ≥ 3mo since Dx NR ≥ 18 years Able to fill out questionnaires and take BP and weight measurements Internet access All cause mort HF mort CV mort Hx HF # Days for HHF HR-QoL (MLHFQ) 19. Wita et al [ 58 ] I: TM with App in tab C: UC (Cardiology Clinic) I: 28 C: 32 I: 65.1 (11.7) C: 66.9 (9.3) I: 23 (82.1) C: 24 (75) NR I: 26.6 (7) C: 26.1 (6.7) I: Isq 13 (46.4) C: Isq 16 (50) 24 HF with reduced LVEF, candidates for CRT according to ESC 2013 guidelines NR NR All cause mort HHF SD standard deviation, IQR interquartile range, NYHA New York Heart Association, LVEF left ventricular ejection fraction, HF heart failure, Hx hospitalizations, C comparator, I intervention, Tx treatment, TM telemonitoring, MPh mobile phone, UC usual care, HT hypertensive, mo months, def definition, ESC European Society of Cardiology, OMT optimal medical therapy, ACEi angiotensin-converting enzyme inhibitor, ARB - II angiotensin II receptor antagonist, BB beta blocker, wk weeks, mort mortality, CV ...…”
Section: Resultsmentioning
confidence: 99%
“…monthly Man NR e-Vita Platform Alarm if OOGM or if no data registration Nurse: Contact pt if OOGM—> query sto, TxMod, indicate consultation NR 19. Wita et al [ 58 ] NR (Developed by Meditel Company in Poland) App in tab Scale BPM 3-lead ECG Weight BP Sto Freq. Q.D ECG every week Man NR Management based on trends of previous week parameters Possibility of teleconsultation NR app application, os operating system, FdB feedback, fun functionalities, w - App web application, MPh mobile phone, IBI issued bt investigators, BPM sphygmomanometer, auto automated, HR heart rate, BP blood pressure, freq frequency, DoM dosing of medication, Q .…”
Section: Resultsmentioning
confidence: 99%
“…15,[18][19][20][21][22][23][24] The other 19 studies used non-invasive devices. 9,14,16,17,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] While most of the usual care/control groups were categorized for in-clinic follow-up only, there were 3 studies which allowed for the patients in the control group to occasionally contact their physician/nurse. 25,31,33 All of the noninvasive interventions monitored the patients using standard telephone/telemonitored/telehealth features interactively.…”
Section: General Characteristics Of Included Trialsmentioning
confidence: 99%
“…In psychiatry and rehabilitation, a meta-analysis reviewing 43 studies of high methodological quality detected no significant difference between TM and face to face services (8). A recent study from Poland published 2021 have concluded that tele-monitoring of patients with CRT has improved their prognosis during the 2 years observation period and also decreased the rate of hospitalization significantly (9). A meta-analysis of 19 RCTs have showed that tele-monitoring in patients with Heart Failure has reduced hospitalization significantly with an Odds Ratio of 0.83 (95% CI 0.72-0.95, P = 0.007) (10).…”
Section: Advantages Of Remote Medical Services In Other Societiesmentioning
confidence: 99%